A Socio-legal study on financial rights of Muslim divorced women and its effect on family welfare - Muslihah binti Hasbullah @ Abdullah (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2009)
The purpose of this study is two-fold: Firstly, to examine the law relating to financial rights of the divorced Muslim women in terms of 'iddah maintenance, arrears of maintenance, mut'ah, and child maintenance. Secondly, to assess the welfare of the women after divorce i.e., satisfaction with the amount of financial supports; satisfaction with the ex-husbands' compliance to court orders on financial supports; satisfaction with post-divorce welfare (level of economic strain and level of depression); relationships between satisfaction with the amount of financial supports and post-divorce welfare; and relationships between satisfaction with the exhusbands' compliance to court orders and post-divorce welfare. This study adopts the qualitative and quantitative methods that are necessary for a socio-legal research. The qualitative method draws data from the Syariah principles, classical texts of the Muslim jurists, contemporary legal writings, the Malaysian Islamic family laws, legislations from other jurisdictions where Islamic law is applicable, and case law. The quantitative method employs the statistical tool, i.e., Statistical Package for Social Sciences (SPSS) for Windows Program Version 13.0 to collect data on the welfare of the divorced women. Two statistical procedures, i.e., descriptive and inferential statistics were used to analyze the empirical data. The findings of this study suggest that the Syariah judges should develop their judgments on financial supports' cases based on the welfare principle (maslahah) as articulated by the classical Muslim jurists. Such principle should be construed within the meaning of the current contexts of economic needs, social demands, and psychological effects of divorce on women and applied the best approach for which safeguarding human welfare is the primary aim of the maqasid al-Shari'ah. The Pearson's Product Moment Correlation Coefficient employed for the empirical data suggests two factors that are negatively correlated with the economic welfare of the divorced women i.e., the dissatisfaction with the amount of financial supports and the dissatisfaction with the ex-husbands' compliance to court orders particularly on 'iddah maintenance, mut'ah, and child maintenance. The findings indicate that the assessment of a reasonable sum of financial supports and the effective enforcement of court order are the significant factors that might augment the economic welfare of the women after divorce. Hence, the typically low amount of financial supports ordered by the Syariah court should be reviewed by providing clear guidelines on the factors that need to be considered based on the demand in the contemporary society. Besides, tougher enforcement action by prosecuting the unruly ex-husbands and the establishment of administrative machinery might assist the divorced women to effectively enforce the court order.